Bajar del cerro: el paisaje, los héroes culturales y la música en las narrativas fundacionales de dos comunidades del lago de Pátzcuaro (El Hilo de la Fabula, 2020)
This article presents and analyzes a group of oral narratives that covers the foundation of two indigenous towns in the state of Michoacán —Ihuatzio and Santa Fe de la Laguna—,located in western Mexico. The stories were documented as part of a research project that registered oral traditions in the area of Lake Pátzcuaro, a region historically marked as having been the center of the Purhepecha culture. After dis- cussing some questions about the historical context and the cultural importance of these narratives, this article presents a structural and symbolic analysis of the stories. This analysis aims to show how the poetics of these oral narratives build a complex network of meanings in which actions, characters and symbols, weave geographical, musical and historical di- mensions.
Keywords: Oral Narrative; Mexico; Michoacán; Purhépecha; Mythology; Indigenous peoples